Identification of a novel COL10A1: c.1952 G>T variant in a family with Schmid metaphyseal chondrodysplasia and development of a noninvasive prenatal testing method - Yanchou Ye (Wiley, 2021)
Abstract Background The collagen alpha‐1(X) chain gene (COL10A1) is a known causative gene for Schmid metaphyseal chondrodysplasia (SMCD). This study clinically examined a Chinese family (n = 42) for SMCD and inheritance pattern. Fifteen individuals were diagnosed with SMCD based on characteristic skeletal phenotypes with autosomal dominant inheritance mode. Methods Four clinically diagnosed patients and three healthy relatives were selected for subsequent genetic tests. Trio‐whole exome sequencing (Trio‐WES) followed by Sanger sequencing and familial co‐segregation analysis were performed to identify SMCD‐associated variants. Results COL10A1 (NM_000493.4):c.1952 G>T(p.Trp651Leu) variant was detected only in the four patients and not in the three healthy relatives. The variant was evaluated as “likely pathogenic” according to the American College of Medical Genetics and Genomics variation classification guidelines with evidence of PM2, PM5, PP1, and PP3. To test the presence of the target variant in proband's fetal offspring, we developed a noninvasive prenatal testing method by extracting cell‐free fetal DNA in maternal plasma followed by high‐depth sequencing. The variant was also detected in the fetus and later confirmed by amniocentesis. Conclusion We identified a new disease‐causing variant in COL10A1. Cell‐free fetal DNA in maternal peripheral blood can be used as the rapid and noninvasive prenatal diagnostic method to detect the pathogenic/or likely pathogenic variant.